2015
DOI: 10.1016/j.fuproc.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic analysis of crude rapeseed oil flame

Abstract: Utilizing crude vegetable oils in all types of heat engines can be a part of sustainable economy in the future. Focusing on their local usage, they can possibly compete with fossil fuels. Furthermore, to keep the pollutant emissions at the lowest possible level, the feedback control of the equivalence ratio is essential. Regarding the harsh environment of the combustion chambers, optical flame diagnostics is a potential tool. Therefore, in order to examine its feasibility, the comparison of flame emission spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Finally, the uncertainty of the positioning system of the spectrometer is 1 mm both horizontally and vertically. Further details of the spectrometer can be found in the literature [36,37].…”
Section: The Fes Measurementmentioning
confidence: 99%
“…Finally, the uncertainty of the positioning system of the spectrometer is 1 mm both horizontally and vertically. Further details of the spectrometer can be found in the literature [36,37].…”
Section: The Fes Measurementmentioning
confidence: 99%
“…Our previous combustion studies revealed that atomization characteristics considerably affect the flame shape, pollutants, and chemiluminescence emissions (Józsa and Kun-balog, 2015;Józsa and Sztankó, 2016;Kun-Balog and Sztankó, 2015). In order to analyze both local and global spray characteristics, the plain-jet airblast atomizer was examined in cooperation with the Brno University of Technology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presented method is conservative. More details about the experiments related to this burner can be found in the literature (see, e.g., [9,13]). …”
Section: The Investigated Burnermentioning
confidence: 99%
“…In practical devices, the combustion power demand is given rather than the fuel flow rate. Consequently, SMD calculations were carried out keeping 15 kW of firing power, which comes from the previous experimental studies [9,13].…”
Section: D T Hu E H U Humentioning
confidence: 99%
See 1 more Smart Citation